The Robert Wood Johnson Nurse Faculty Scholars Diversity and Inclusion Research - Versie Johnson-Mallard; Randy Jones; Maren Coffman; Jacinta Gauda; Katie Deming; Mario Pacheco; Jacquelyn Campbell (Mary Ann Liebert, 2019)
Purpose: The purpose of this research is to deepen the understanding of DEI training and show how scholars across the nation incorporated DEI leadership into academic roles. Faculty and administrators' experiential experience in diversity, equity, and inclusion (DEI) plays a role in the success or failure of DEI training. DEI training at institutes of higher learning should include metrics that examine our bias for invisible and overt support for DEI. Methods: Robert Wood Johnson Foundation Nurse Faculty Scholars (RWJFNFS) were surveyed by The Gauda Group at Grayling. Data were collected from a diverse group of scholars across the nation. An online survey followed by an in-depth phone interview was used to assess participants' roles as leaders in academic nursing, challenges faced by scholars in addressing DEI, and perceived values of undertaking DEI activities. Results: Major themes emerged from the findings. The themes included championing for DEI comes with a personal and professional risk. Greater success was noted when DEI was supported by leadership and included in institutional strategic planning. Conclusion: DEI is important and necessitates commitment from all levels of leadership, faculty, and strategic planning initiatives. DEI training fills an important role and subsidizes leadership effectiveness as it relates to DEI.